Management of Paralytic Ileus - Elizabeth Merry Wintery; Ari Fahrial Syam; Marcellus Simadibrata; Chudahman Manan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Ileus is a pathophysiologic state of inhibited motility in the gastrointestinal tract due to a physical/ anatomic obstruction in the lumen (obstructive ileus) or due to cessation of smooth muscle motor activity in the small intestine and colon. In Internal Medicine, paralytic ileus is most commonly caused by peritonitis, which is most often caused by acute pancreatitis. To establish a diagnosis, several diagnosis evaluation procedures may need to be performed such as laboratory evaluation, radiologic examination, ultrasonography and CT examination. Management of paralytic ileus is aimed at the underlying disease and supportive therapy. With this management paralytic ileus will spontaneously remit. Keywords: paralytic ileus, pathogenesis, diagnosis, management